2010
DOI: 10.2174/1874192401004010231
|View full text |Cite
|
Sign up to set email alerts
|

Animal Models of Cardiac Disease and Stem Cell Therapy

Abstract: Animal models that mimic cardiovascular diseases are indispensable tools for understanding the mechanisms underlying the diseases at the cellular and molecular level. This review focuses on various methods in preclinical research to create small animal models of cardiac diseases, such as myocardial infarction, dilated cardiomyopathy, heart failure, myocarditis and cardiac hypertrophy, and the related stem cell treatment for these diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 149 publications
1
18
0
Order By: Relevance
“…Use of isoproterenol (ISO), a β adrenergic agonist and a synthesized catecholamine, has been done since long time for studying the efficacy of newer molecules against MI in animal model [13]. ISO has been known to produce MI in quantity above therapeutic dose, through production of elevated levels of free radicals by undergoing oxidation, and thereby induce cytotoxicity [14,15]. These oxidative remainders are known for further modulation of the myocardial tissue functionality.…”
Section: Introductionmentioning
confidence: 99%
“…Use of isoproterenol (ISO), a β adrenergic agonist and a synthesized catecholamine, has been done since long time for studying the efficacy of newer molecules against MI in animal model [13]. ISO has been known to produce MI in quantity above therapeutic dose, through production of elevated levels of free radicals by undergoing oxidation, and thereby induce cytotoxicity [14,15]. These oxidative remainders are known for further modulation of the myocardial tissue functionality.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that cTnI is a protein associated with the myocyte contractile apparatus, which will be released into the serum when myocytes are injured and can serve as a marker of myocyte injury [21]. cTnI is highly sensitive and specific for myocarditis in mice 17-21 days after MyHCa immunization [22]. We found that insulin treatment lowered serum cTnI levels of EAM mice significantly on days 14 (P < 0·05) and 21 (P < 0·05) compared with the saline-treated group.…”
Section: Discussionmentioning
confidence: 99%
“…In MI-Magnet + MNBs/Ad hVEGF , MI-MNBs, and MI-Magnet + MNBs/Ad GFP groups, MI was induced as described earlier [24][26]. Briefly the left anterior descending coronary artery(LAD)was ligated permanently.…”
Section: Methodsmentioning
confidence: 99%